Central Nervous System Inflammation Induced by Lipopolysaccharide Up-Regulates Hepatic Hepcidin Expression by Activating the IL-6/JAK2/STAT3 Pathway in Mice - Zhang, Fali; Zhao, Peng; Qian, Zhongming; Zhong, Mingkang (Frontiers in Nutrition, 2021)
It is known that lipopolysaccharide (LPS) triggers inflammatory response after intracerebroventricular (ICV) injection and elevates the expression of hepcidin through the interleukin 6/janus kinase 2/transducer and activator of the transcription 3 (IL-6/JAK2/STAT3) signaling pathway in the brain. This study was conducted to determine whether LPS ICV injection can regulate peripheral hepatic hepcidin expression and iron metabolism. Here, we studied the hepcidin expression in the liver, as well as serum iron and transferrin saturation, after LPS ICV injection. We also demonstrated the role of the IL-6/JAK2/STAT3 pathway in hepcidin expression in the livers of IL-6 knockout (IL-6-/- mice) and IL-6+/+ mice. AG490 was used to verify the effect of the IL-6/JAK2/STAT3 pathway on hepatic hepcidin expression. Our present study demonstrated that LPS ICV injection up-regulated hepatic hepcidin expression. This finding provides further evidence for highlighting the importance of the central inflammation on hepatic hepcidin expression and peripheral iron metabolism.